2013
DOI: 10.1177/0899764013485159
|View full text |Cite
|
Sign up to set email alerts
|

The Social Network Effect

Abstract: Social networking applications such as Facebook, Twitter, and Crowdrise offer new ways for nonprofits to engage the community in fundraising efforts. This study employs data from Facebook Causes to examine the nature and determinants of charitable giving in social networking environments. Our findings suggest donations on these sites are not driven by the same factors as in “off-line” settings. Instead, a social network effect takes precedence over traditional economic explanations. Facebook donors do not seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(133 citation statements)
references
References 28 publications
(38 reference statements)
4
122
0
7
Order By: Relevance
“…Although they have not considered the distance of ties between donors and musicians, Mollick (2014) and Zheng et al (2014) identified a positive relationship between the number of social contacts identified on Facebook or other social networks (e.g., Weibo Page, a Chinese social network) with the amount donated and with the musical project's performance. These results are also supported by Saxton and Wang (2014), who found that nonprofit organizations with more Facebook fans receive more donations, and by Colombo et al (2015), who found that greater numbers of contacts on Linkedin were associated with both the number of supporters and the volume of capital raised in 669 projects on the Kickstarter platform.…”
Section: Literature Review and Hypothesessupporting
confidence: 72%
See 3 more Smart Citations
“…Although they have not considered the distance of ties between donors and musicians, Mollick (2014) and Zheng et al (2014) identified a positive relationship between the number of social contacts identified on Facebook or other social networks (e.g., Weibo Page, a Chinese social network) with the amount donated and with the musical project's performance. These results are also supported by Saxton and Wang (2014), who found that nonprofit organizations with more Facebook fans receive more donations, and by Colombo et al (2015), who found that greater numbers of contacts on Linkedin were associated with both the number of supporters and the volume of capital raised in 669 projects on the Kickstarter platform.…”
Section: Literature Review and Hypothesessupporting
confidence: 72%
“…Thus, it is expected that the investors who are not socially connected to the entrepreneurs tend to take longer amounts to donate than others. Nevertheless, donors with close ties to the musicians tend to donate larger amounts (Saxton and Wang 2014). Given the above reasons, we believe that the greater the exposure time of the project is, the greater the value of the donations will be.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of Italians tweeting about elections found a connection between getting more information from Twitter and participating more in the elections, although no cause and effect relationship was established (Vaccari et al, 2015). Similarly, social media strategies can be successful at eliciting small donations, especially for health organizations Wang, 2014).…”
Section: Reaching An Audience On Twittermentioning
confidence: 99%